Social smerte i det moderne arbejdsliv ud fra et arbejdspsykologisk perspektiv - Baldursson, Einar Baldvin (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
It is often argued, that modern work and living in globalized knowledge society involve new demands and social stressors. This paper argues that it is meaningful to assume the existence of a psychological immune system that has emerged through the evolution of social mammals and humans. Accord to the theory, this system is activated in the case of social threats, loss or damage. When activated it causes psychological pain and depressive reaction. Similar to the innate immune system, the psychological immune system involves (social) behavior with the goal to limit damage and improve the odds for recovery. In the paper it is argued that modern work involves increased focus on social relations and cooperation. The experience of permanent changes at work, increased pressure and emotional demands lead to increasing risk for social loss and defeat at work. According to this theory such experiences will lead to psychological pain and depressive mental states. This theory can contribute to explaining the increasing prevalence of stress and depression.